Very Urgent: Music of Desperation and Purpose in the Oakland of 2020 - Evangelista, Karl (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Guitarist/composer Karl Evangelista writes of the quarantine projects that he carried out from his home in Oakland, California: two album releases—one with South African drummer-activist Louis Moholo-Moholo and one with art rock/experimental project Grex—and the curation of two online “Lockdown Festivals.”